Kebijakan Pembangunan Industri Dan Lingkungan Terhadap Pembangunan Daerah Surabaya - Melinda Wirastiti; Syahrizal Zebua; Aditya Arga Widhyasa; Muhammad Yasin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Industrial development by concentrating industries in a place, which is called an industrial area, is intended to suppress the spread of environmental impacts caused by industry. Another goal is that the presence of industry in the same place will have a double effect on society. However, these objectives must be followed by the fulfillment of strict criteria. These criteria start from the determination of land allocation for industrial estates, to the obligation to manage waste or environmental impacts caused. The industrial estate development policy must pay attention to environmental aspects, thus building an environmentally sound industrial estate.